Studi Perhitungan Rele Tanah (GFR) Akibat Gangguan Simpatetik Trip Pada Penyulang Tegangan Menengah - Samsurizal Samsurizal; Tito Ganjar Nugroho (Sekolah Tinggi Teknik - PLN, 2020)
Disturbances are generally in the form of short circuits which produce large short-circuit currents, so a protection system is needed to be able to minimize the extent of the impact of the fault current. In medium voltage networks, protection is needed to secure the network from interference along the conduit. The problem that often occurs in medium voltage network systems is sympathetic trip disorder, namely the failure of the relay in the uninterrupted feeder to join the trip together with the interrupted feeder. This incident occurred in the Windu feeder when there was a short circuit interruption of the single phase of the ground feeder at the Kosambi Duri Substation. Based on these events will be discussed how the influence of the disturbance current flowing to the point of disturbance and passing through the feeder relay, for that reason there needs to be an analysis related to setting the working time of the ground relay on the feeder. From the calculation results when there is a disturbance in the compact feeder where the ground work time relay is worth 0.294 seconds (working) and for Windu feeder when the compact is disturbed it is -0.333. This minus value means that the relay should not work. It is suspected that Windu's feeder sympathetic is caused by an increase in phase voltage and creates new interference.